(untitled) (JONAH : Journal of Nursing and Homecare, 2024)
Nausea often occur in pregnant in the first trimester or early stages of pregnancy, where the management of nausea is mostly done by pharmacological means which can impact on the mother and the organogenesis period in the fetus. Prolonged nausea in pregnant can cause dehydration, nutritional deficiencies, and negative impacts on the fetus including birth defects and miscarriage. Purpose to determine the implementation of a combination of acupressure pericardium 6 and peppermint aromatherapy to reduce nausea. This type of research is a descriptive case study in a case study, one pregnant who experiences mild nausea, this data collection uses interviews using a questionnaire, this research was conducted on April 29-May 01, 2024, the analysis technique used is qualitative by describing and drawing conclusions based on the results obtained during the study. The results obtained during the 3 days of implementation on the first day of the PUQE score was 13, on the second day it decreased after being given an implementation of 7, and the third day decreased again with a score of 3. The combination of P6 acupressure and aromatherapy reduces nausea and vomiting in pregnant.